Poor Sleep Quality is Linked to Elevated Extracellular Vesicle-Associated Inflammatory Cytokines in Warfighters With Chronic Mild Traumatic Brain Injuries - Gottshall, Jackie L.; Guedes, Vivian A.; Pucci, Josephine U.; Brooks, Daniel; Watson, Nora; Sheth, Phorum; Gabriel, Ainslee; Mithani, Sara; Leete, Jacqueline J.; Lai, Chen; Qu, Bao-Xi; Devoto, Christina; et al. (Frontiers in Pharmacology, 2022)
Background. Elevations of inflammatory cytokine levels occur immediately after mTBI and can persist for years. These elevations have been associated with neuropsychological outcomes, including depression and PTSD symptoms. Sleep disorders, another common sequelae of mTBI, are independently associated with inflammation in otherwise healthy individuals. However, whether sleep and inflammation are linked in chronic mTBI has not been reported. Methods. A retrospective cross-sectional cohort of warfighters was used to investigate the hypothesis that inflammation may be linked to sleep quality in chronic mTBI. Clinical history, peripheral blood samples, and sleep quality scores were collected from 182 warfighters (n=138 mTBI; n=44 controls) during enrollment in the Chronic Effects of Neurotrauma Consortium study. Biomarkers of inflammation (IL-6, IL-10, TNFα cytokines) from plasma and plasma-derived extracellular vesicles (EVs) were quantified using single molecule array. Relationships between sleep quality and cytokine levels were assessed, controlling for age, sex, and BMI. Using clinical cutoff scores for sleep quality, mTBI patients were then divided into “good” and “poor” sleepers and cytokine levels compared between groups. Results. In mTBI participants, sleep quality was significantly associated with EV levels of IL-10 (ß (SE) = 0.11 (0.04), p = .01) and TNFα (ß (SE) = 0.07 (0.03), p < .01). When divided according to “good” versus “poor” sleepers, those reporting poor sleep had significantly elevated EV IL-10 compared to those reporting good sleep (ß (SE) = 0.12 (0.04), p < .01). Plasma-derived associations were not significant. No associations were found between sleep quality and cytokine levels in controls. Conclusions. These results suggest a significant relationship between sleep quality and chronic inflammation in mTBI patients. Clinically, mTBI patients with a high likelihood of sleep disorders demonstrate elevated levels of inflammatory cytokines. Signal from EVs, though smaller in magnitude, may have stronger clinical associations than from plasma. Sleep-focused interventions may also serve to regulate chronic inflammatory processes in these patients. Larger prospective studies are needed to investigate the mechanisms and therapeutic implications of the likely bi-directional relationship between sleep and inflammation following mTBI.